MAKNA keselamatan dalam perspektif agama-agama / Budi Raharjo...[et al] ; editor Ignatius Loyola Madya Utama. - Budi Raharjo; Ignatius Loyola Madya Utama (Universitas Sanata Dharma, 2014)
viii, 165 hlm. ; 21 cm